Commentary on the constituion of India: Arts. 282-307 - Durga Das Basu; BASU (Durga Das) (Calcutta S C Sarkar & Sons Pvt Ltd, 1986)
Key features: pioneering work on the indian constitution first authoritative work on the constitution of india that adopted an interdisciplinary approach, examining the constitution from the philosophical, sociological, political as well as legal perspectives. First book to study and comparatively analyze other constitutions, including countries that do not belong to the anglo-american jurisprudential tradition.
Keywords: Constitution of India; Finance; Borrowing; Right to Property; Trade